2002
DOI: 10.1136/bmj.324.7328.23
|View full text |Cite
|
Sign up to set email alerts
|

Education, income inequality, and mortality: a multiple regression analysis

Abstract: Objective To test whether the relation between income inequality and mortality found in US states is because of different levels of formal education. Design Cross sectional, multiple regression analysis. Setting All US states and the District of Columbia (n = 51). Data sources US census statistics and vital statistics for the years 1989 and 1990. Main outcome measure Multiple regression analysis with age adjusted mortality from all causes as the dependent variable and 3 independent variables-the Gini coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
3
18

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(142 citation statements)
references
References 15 publications
5
116
3
18
Order By: Relevance
“…Ahluwalia & Bolen (2008) represent lifetime e↵ects of socioeconomic limitations, and may influence future occupational opportunities and earning potential. Higher educational degrees are typical prerequisites for highly compensated work, which allows a↵ordability of health insurance coverage and access to high-quality care (Muller, 2002). Similar to the finding of the previous literature, our results show that non-Hispanic whites are more likely than any other race/group to have insurance coverage (Ahluwalia & Bolen, 2008;Cohen & Martinez, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Ahluwalia & Bolen (2008) represent lifetime e↵ects of socioeconomic limitations, and may influence future occupational opportunities and earning potential. Higher educational degrees are typical prerequisites for highly compensated work, which allows a↵ordability of health insurance coverage and access to high-quality care (Muller, 2002). Similar to the finding of the previous literature, our results show that non-Hispanic whites are more likely than any other race/group to have insurance coverage (Ahluwalia & Bolen, 2008;Cohen & Martinez, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…The racial disparities in health insurance are strongly associated with socioeconomic factors: African Americans and Hispanics face greater economic and educational barriers than other groups and have less access to high-paying jobs that facilitate access to health care and health care coverage. Compared with non-Hispanic whites, non-Hispanic blacks and Hispanics tend to have higher rates of unemployment and under-representation in good-paying jobs that include health insurance as part of the benefit package (Muller, 2002). Furthermore, individuals from racially or ethnically diverse backgrounds make up a great majority of the uninsured population (Cohen & Martinez, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that education may be such a determinant, because it has been linked to mortality risks both between and within countries, including in natural experiments (1)(2)(3)(4).…”
Section: Epidemiology | Natural Experimentsmentioning
confidence: 99%
“…Previous studies have importantly shown that the compositional effect of income on health may generate a spurious association between inequality and health (Jen et al 2008). Previous study has also identified a negative association between inequality and education as a potential cause of the association between inequality and health (Muller 2002).…”
Section: Covariatesmentioning
confidence: 99%